2022
DOI: 10.1111/mec.16594
|View full text |Cite
|
Sign up to set email alerts
|

Linking large‐scale genetic structure of three Argynnini butterfly species to geography and environment

Abstract: Understanding which factors and processes are associated with genetic differentiation within and among species remains a major goal in evolutionary biology. To explore differences and similarities in genetic structure and its association with geographical and climatic factors in sympatric sister species, we conducted a large-scale (>32°

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 150 publications
9
14
1
Order By: Relevance
“…These results are consistent with the findings of Polic et al (2022) covering the entire Western Palaearctic and using a large number of sequence‐based markers. Their A. adippe samples from most of Europe formed a single genetic unit, differentiated only from the Iberian Peninsula.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with the findings of Polic et al (2022) covering the entire Western Palaearctic and using a large number of sequence‐based markers. Their A. adippe samples from most of Europe formed a single genetic unit, differentiated only from the Iberian Peninsula.…”
Section: Discussionsupporting
confidence: 92%
“…In A. niobe , the situation in Central Europe was complex, with samples from the Alps linked to more westerly samples, and those from the Carpathians linked to the Balkans. Thus, both our results and those of Polic et al (2022) point to genetic interconnection of A. adippe across Central Europe, and to intermixing of A. niobe lineages, which probably formed during Pleistocene climate and habitat changes (e.g., Bartonova et al, 2020; Hammouti et al, 2010), in the area between the Carpathian Arc and the Balkans.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This may be particularly prevalent in species with large populations (Gillespie 2000) or in species that have experienced rapid range expansions (Petit and Excoffier 2009). Similar discordant results were detected in Speyeria aglaja (Lepidoptera: Nymphalidae) (Polic et al 2022), where distinct geographic lineages were detected with genome-wide SNPs but not with CO1 haplotypes. Polic et al (2022) suggested that gene flow or selective sweeps homogenised haplotype diversity and erased the spatial variation in the mitochondrial genome.…”
Section: Mitonuclear Discordancesupporting
confidence: 63%
“…Intraspecific variation, especially if it is recently derived, often necessitates large numbers of independent and variable loci to accurately infer population and demographic histories and to resolve spatial genomic variation (Hey and Nielsen 2004;Carling and Brumfield 2007;Gompert et al 2014;Garrick et al 2015;Satler et al 2021). Recent technological advances provide access to single nucleotide polymorphisms (SNPs) spread throughout the genome (Baird et al 2008;Peterson et al 2012;McCormack et al 2013;Garrick et al 2015) and have been used successfully to resolve spatial genetic variation in many widespread, nonmodel organisms (e.g., Bagley et al 2017;Lumley et al 2020;MacDonald et al 2020;Cairns et al 2021;Polic et al 2022).…”
Section: Introductionmentioning
confidence: 99%